Reversibility of Liver Fibrosis - Sun, Mengxi (Clin Res Hepatol Gastroenterol, 2015)
Liver fibrosis is a serious health problem worldwide, which can be induced by a wide spectrum of chronic liver injuries. However, until today, there is no effective therapy available for liver fibrosis except the removal of underlying etiology or liver transplantation. Recent studies indicate that liver fibrosis is reversible when the causative agent (s) is removed. Understanding of mechanisms of liver fibrosis regression will lead to the identification of new therapeutic targets for liver fibrosis. This review summarizes recent research progress on mechanisms of reversibility of liver fibrosis. While most of the research has been focused on HSCs/myofibroblasts and inflammatory pathways, the crosstalk between different organs, various cell types and multiple signaling pathways should not be overlooked. Future studies that lead to fully understanding of the crosstalk between different cell types and the molecular mechanism underlying the reversibility of liver fibrosis will definitely give rise to new therapeutic strategies to treat liver fibrosis.